Residual embryonic cells as precursors of a Barrett's-like metaplasia. - Wang, X; Ouyang, H; Yamamoto, Y; Kumar, P; Wei, T; Dagher, R; Vincent, M; Lu, X; Bellizzi, A; Ho, K; Crum, C; Xian, W; et al. (2011)
Barrett's esophagus is an intestine-like metaplasia and precursor of esophageal adenocarcinoma. Triggered by gastroesophageal reflux disease, the origin of this metaplasia remains unknown. p63-deficient mice, which lack squamous epithelia, may model acid-reflux damage. We show here that p63 null embryos rapidly develop intestine-like metaplasia with gene expression profiles similar to Barrett's metaplasia. We track its source to a unique embryonic epithelium that is normally undermined and replaced by p63-expressing cells. Significantly, we show that a discrete population of these embryonic cells persists in adult mice and humans at the squamocolumnar junction, the source of Barrett's metaplasia. We show that upon programmed damage to the squamous epithelium, these embryonic cells migrate toward adjacent, specialized squamous cells in a process that may recapitulate early Barrett's. Our findings suggest that certain precancerous lesions, such as Barrett's, initiate not from genetic alterations but from competitive interactions between cell lineages driven by opportunity.